Assessment of Filtered Water Quality Using a Simple Filtration System in Kalikayen Village, Semarang Regency - Sriwanto; Hendra Masvika; Lilla Angraini; Bambang Tutuko (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2026)
Access to water with acceptable quality remains an important issue in rural communities that rely on surface water or groundwater for domestic activities. This study evaluated the performance of a simple gravity-fed filtration system using gravel, silica sand, activated carbon, and manganese zeolite as filter media for improving water quality in Kalikayen Village, East Ungaran District, Semarang Regency. Water samples were collected before and after filtration and analyzed at the Health Laboratory Technical Implementation Unit of Semarang City for total ammonia, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), and pH. The results showed that filtration reduced total ammonia from 0.78 to 0.17 mg/L and TSS from 50 to 3 mg/L, indicating substantial removal of suspended and ammonia-related contaminants. However, BOD increased from 0.44 to 1.19 mg/L, while COD remained below 0.50 mg/L before and after filtration. The pH decreased slightly from 7.60 to 7.46 but remained near neutral. Overall, the multi-media filtration system substantially improved selected water-quality characteristics, particularly TSS and total ammonia, although the increase in BOD indicates that further investigation of organic matter behavior and filter operation is required. The findings demonstrate the potential of a low-cost gravity-fed filtration system as a practical preliminary water-treatment option for rural communities.